"If You Have a Kid That's Ready to Learn:" the Kindergarten Transition Experiences of Urban, Low-Income, African-American Preschoolers. Issue 3 (16th April 2019) - Jarrett, Robin L.; Coba-Rodriguez, Sarai
ABSTRACT: Research suggests that children from urban, low-income African-American families lack school readiness skills and will experience challenging kindergarten transitions. Such studies emphasize family and child deficits. Addressing this gap, we conducted qualitative interviews before and at the end of kindergarten with 12 inner-city, low-income, African-American mothers of Head Start preschoolers. During both periods, mothers assessed children's readiness skills, and provided home-based support. At the end of kindergarten, despite challenges, children's transitions were overwhelmingly positive. Our findings suggest how preschools and schools can promote children's successful transitions, including families' home-based strategies.